Comparing different methods for diagnosis of human papilloma virus infection of the cervix in Egyptian women. Issue 3 (August 2016) - Badeeh, Mona A.; Zol-Fokar, Dalia; Ali, Eman; Shaker, Olfat; Hosni, Hala
Abstract : Objective: The aim of the study was to compare human papilloma virus (HPV) detection by PCR in-situ hybridization (PCR-ISH) of tissue, which is the golden standard test, with PCR swabs and other available conventional techniques such as cytology, histopathology, and colposcopy to determine which of these techniques can be relied upon in a developing country like Egypt with low resources. Patients and methods: Patients referred from the gynecological outpatient clinic for colposcopic examination because of abnormal Pap smear or abnormal-looking cervices were recruited into the study. Each selected patient was subjected to history taking, clinical examination, abdominal examination, and colposcopic examination using a Welch ALLYN digital colposcope. The Pap smear was taken using Ayre's spatula if not done before. Cervical swab was taken for HPV-DNA extraction and detection by PCR using specific primers. The green filter was applied to detect abnormal vessels. Acetic acid 3% was applied to the cervix and Schiller's iodine test using Lugol's iodine was carried out. The area with no iodine uptake especially if preceded by acetowhite was considered abnormal and multiple biopsies were taken for histopathological examination and for PCR-ISH of tissue. Results: The study included 30 patients: 10 (33.33%) showed abnormal cytology and the other 20 (66.67%) showed acetowhite areas in the transformation zone on colposcopic examination. In this study the golden standard test for HPV detection was PCR-ISH, which was negative in 14 (46.67%) cases and positive in 16 (53.33%) cases. There was no statistical difference between the presence of HPV and age, parity, and presence of risk factors. Pap smear results were negative in 13 (43.33%) cases and positive in 17 (56.67%) cases. Low-grade squamous intraepithelial lesion with perinuclear halo represented nearly half of the positive cases (8/17, 47.05%). Compared with PCR-ISH, the sensitivity of Pap smear was 87.50%, specificity was 78.57%, positive predictive value (PPV) was 82.35%, and negative predictive value (NPV) was 84.61%. Histopathology results were negative in six (20%) cases and positive in 24 (80%) cases. Cervical intraepithelial neoplasia grade I (CIN I) and CIN I+koilocytosis represented more than half of the positive cases (15/24, 62.50%). Compared with PCR-ISH, the sensitivity of histopathology was 100%, specificity was 42.85%, PPV was 66.67%, and NPV was 100%. By colposcopic examination an abnormal transformation zone suggestive for HPV was found in 20/30 (66.67%) cases. Compared with PCR-ISH, the sensitivity of colposcopy was 62.50%, specificity was 28.57%, PPV was 50%, and NPV was 40%. By PCR swab, 21 cases were found to be negative for HPV but by PCR-ISH seven of them were positive (false negative). All positive cases ( n =9) remained positive. Compared with PCR-ISH, the sensitivity of PCR swab was 56.25%, specificity was 100%, PPV was 100%, and NPV was 66.67%. Our study showed that histopathology was the most sensitive test for HPV diagnosis and the PCR swab was the most specific test. Conclusion: PCR-ISH is the golden standard for the diagnosis of HPV. The advantage of ISH is that it is performed directly on tissue, which allows localization of the target sequences and correlation with clinical appearance. When augmented by PCR, the sensitivity can be increased, but it has a major disadvantage of being expensive. Our study proved that conventional cytology and histopathological examination were sensitive tests for detection of HPV. Colposcopy had lower sensitivity and specificity but this can be improved by taking multiple biopsies. PCR swab showed the highest specificity and the lowest sensitivity as blood contamination and insufficient amount of cells adversely affect the result.